Investigating the effects of cannabinoids for the reduction of inflammation and sickle cell disease pain (CRISP); A protocol for a randomized double-blind placebo-controlled study - Jordan Bellis; Lydia Monk; Ritika Jhawar; Galia Pollock; Angela Liu; Charleen Jacobs-McFarlane; Brittany McCrary; Jeffrey Glassberg; Susanna Curtis (PLoS ONE, 2026)
Sickle Cell Disease (SCD) is a hemoglobinopathy affecting millions of people globally. Pain, both acute and chronic, affects over half of those living with SCD, but treatment of chronic pain is an ongoing challenge. While opioid treatments are widely used for chronic pain, it’s efficacy is limited, so alternatives must be explored. This protocol outlines a procedure for investigation of dronabinol, an FDA-approved synthetic tetrahydrocannabinol (THC), for the treatment of pain in patients living with SCD and chronic pain. The study is an 8-week, randomized, double-blind placebo-controlled study which aims to assess both the efficacy and safety of this opioid alternative to pain treatment. The study will also track biomarkers of inflammation as THC has demonstrated anti-inflammatory properties, and inflammation is a driver of SCD pain and disease severity. Results from this study have the potential to further clinical understanding of cannabinoids for pain management in Sickle Cell Disease treatment and spark new questions for research.